1260. In Vitro Activity of Eravacycline Against Clinically Significant Bacteria Isolated from Patients with Cancer. (4th December 2021) - Gerges, Bahgat; Prince, Randal; Rosenblatt, Joel; Reitzel, Ruth A; Shelbume, Samuel; Aitken, Samuel L; Aitken, Samuel L; Raad, Issam I; Rolston, Kenneth
Abstract: Background: Bacterial infections are common in patients with cancer (PWC). Many bacteria have developed resistance to currently used antibiotics, posing therapeutic challenges. we evaluated the in vitro activity of eravacycline (a novel fluorocycline) against clinical bacteria recently (2018-2019) isolated from PWC. Methods: All 565 isolates tested were from blood cultures. CLSI approved broth microdilution method was used. Appropriate ATCC controls were included. MIC50, MIC90, MIC ranges and percent susceptibility calculations were made using FDA breakpoints when available. Eravacycline susceptibility breakpoint for most Gram-positive organisms (GPO) is ≤ 0.06 mg/L and for Enterobacterales is ≤ 0.5 mg/L. Results: Eravacycline had potent activity against Staphylococcus aureus (methicillin-susceptible and resistant strains), oxacillin-susceptible coagulase-negative staphylococci (CoNS) including Staphylococcus lugdunensis, viridans group streptococci, beta-hemolytic streptococci . Streptococcus pneumoniae . Bacillus spp., Corynebacterium spp., and Micrococcus spp. It was slightly less active against oxacillin-resistant CoNS, and vancomycin-susceptible Enterococcus faecalis (MIC90 0, 125 mg/L respectively) and was moderately active against vancomycin-resistant Enterococcus faecium (MIC50, 0.06, and MIC90 . 0.25 mg/L). Eravacycline had potent activity against Escherichia coli (including ESBL producing strains), Citrobacter spp., and non-ESBL Klebsiella spp. Eravacycline inhibited 83% of ESBL positive K. pneumoniae, 83% of Enterobacter cloacae, and 80% of carbapenem-resistant Enterobacteriaceae (CRE) isolates at ≤ 0.5 mg/L. The presence of ESBLs increased MIC90 value no more than 2 fold. Eravacycline was also active against many non-fermentative GNB ( Achromobacter spp., Acinetobacter spp., Sphingomonas paucimobilis, and Stenotrophomonas maltophilia ). Table 1. Percent Susceptibility of Gram-negative isolates to Eravacycline Table 2. Percent Susceptibility of Gram-positive isolates to Eravacycline Conclusion: Our data demonstrate that eravacycline has promising activity against clinically significant bacterial pathogens isolated from PWC including many drug resistant strains such as CRE and non–fermentative GNB. it might play an important role in the treatment of bacterial infections in PWC and warrants clinical evolution in this setting. Disclosures: Samuel L. Aitken, PharmD, MPH, BCIDP, Melinta Therapeutoics (Individual(s) Involved: Self): Consultant, Grant/Research Support Kenneth Rolston, MD, Tetraphase Pharmaceuticals (Grant/Research Support)